Vessels from the Quranic perspective: a thematic study / Noor Syahidah Mohamad Akhir, Siti Aisyah Yusof and Azrul Shahimy Mohd Yusof - Mohamad Akhir, Noor Syahidah; Yusof, Siti Aisyah; Mohd Yusof, Azrul Shahimy (Universiti Teknologi MARA, Perlis, 2018)
A vessel is a time-proven form of transportation and is a mentioned mode of transportation in the Qur'an. A vessel is also a symbol of the stature of civilization and technology of a nation or race. In human civilization, this technology has been used as early as Noah's time. This paper examined the terms of the vessel, analyze the function and structure of the vessels mentioned in the Qur'an since Allah's Commandments would have explicit and implicit wisdoms. This study is a qualitative study using content analysis method, thematic method or mawdhu'i as the subject determination. The results showed that the three vessel terms which are issued al-Quran verses from various surahs are al-Fulk, al-Safinah and al-Jawar. The verses are classified according to the three terms and functions of the vessel and are presented in the form of tables and diagrams.